Radiation response and tolerance in planarian stem cells - Yap, ZC (2024)
Ionizing radiation threatens cellular survival, a property strategically exploited in radiotherapy to eradicate cancer cells. However, the efficacy of radiotherapy is impeded by two co-existing challenges: the presence of radiotolerant cancer stem cells capable of withstanding treatment and subsequently driving cancer recurrence; coupled with collateral damage to normal stem cells, which are typically radiosensitive. Despite the pressing demand for radiotherapy, the underlying mechanisms governing radiosensitivity in normal stem cells and radiotolerance in cancer stem cells remain enigmatic, particularly within an in vivo setting. Here, we leverage the planarian Schmidtea mediterranea, which harbours abundant populations of experimentally tractable adult stem cells, as an in vivo model system to investigate stem cell radiation response and recovery. Employing a functional genomics approach, we aim to assess the transcriptional response of planarian stem cells to gamma radiation at both bulk and single-cell levels, as well as to uncover novel genes crucial for planarian radiotolerance.